Procedure for Submission of Motor Vehicle Insurance Claims at PT. Askrida Syariah Insurance Medan Branch - Adisty Anggraini; Tri Inda Fadhila Rahma (Journal of Indonesian Management, 2022)
Askrida Insurance as a company engaged in risk insurance and loss in the future will face fairly stiff competition with other insurance companies, Therefore, in order to survive and be able to compete with other asurnsi companies, there must be more prominent innovations to compete both in terms of product types, prices and intended segments so as to produce products that are able to compete and win competition. From the above explanation, this final task raises the title "Procedure for Filing Motor Vehicle Insurance Claims at PT. Insurance Askrida Medan Branch" Based on the explanation above, the objective is as follows: To find out motor vehicle insurance products at PT. Asuransi Askrida Syariah Medan branch, To find out the procedure for filing motor vehicle insurance claims at PT. Medan branch of Askrida Syariah Insurance.